2021
DOI: 10.32734/injar.v3i3.4912
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Cost and Economic Returns in Rice Production in Ebonyi State, Nigeria

Abstract: Low profit from most staple food production in Nigeria, have continued to discourage the teaming unemployed Nigerian youth from taking up farming as a business. Therefore, this study analyzes the cost and economic returns in Ebonyi State rice production. This study made used of simple random sampling techniques to select 242 rice farmers. The study employed the use of structured questionnaire in its primary data collection. The collected data were analyzed using descriptive statistics (Percentages, Frequency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…The benefit-cost ratio is used in different analyses to compare profitability between enterprises or groups [67]. For this study, the result indicated ratios of 1.85 and 1.67 for the beneficiaries and non-beneficiaries, respectively, consistent with the conclusion of [39,68] in their analysis of rice profitability in Ebonyi state, Nigeria.…”
Section: Cost and Return Analysis Of Rice Production In Kripsupporting
confidence: 72%
See 1 more Smart Citation
“…The benefit-cost ratio is used in different analyses to compare profitability between enterprises or groups [67]. For this study, the result indicated ratios of 1.85 and 1.67 for the beneficiaries and non-beneficiaries, respectively, consistent with the conclusion of [39,68] in their analysis of rice profitability in Ebonyi state, Nigeria.…”
Section: Cost and Return Analysis Of Rice Production In Kripsupporting
confidence: 72%
“…35 kg m 3 , are not comparable to the world average's paddy output of 4.3 t ha −1 and WP of 0.58-1.23 kg m 3 [38]. Various studies have studied the efficiency of paddy production in Nigeria [9,16,39]. However, there has been no study on IWUE in rice production.…”
Section: Introductionmentioning
confidence: 94%
“…The level of paddy field farming revenue in the study area is substantially higher than in other studies, such as Karmini [9], Arifin et al [10], and Arifin et al [11] but slightly lower than the findings of Wardana et al [12] with a revenue of Rp. 9.143.061 per growing season, and Nwahia [13] with an revenue level of Rp. 10.034.000 per growing season.…”
Section: Paddy Field Cost and Income Analysismentioning
confidence: 99%
“…Profitability analysis by Nwahia [2020] found that rice farmers earned an average net farm income of $900.10/ha (N323,135.90/ha with a return on investment of 2.9% in South East Ebonyi State of Nigeria [32]. Usman [2020] reported that the net farm income for mechanized and nonmechanized maize farmers' was N310,100.00/ha and N127,950.00/ha respectively n Kaduna State, Nigeria [47].…”
Section: Empirical Reviewmentioning
confidence: 99%